Penerapan Metode “Make A Match” untuk Meningkatkan Minat Belajar dalam Kemampuan Menulis (Kitabah) Mata Kuliah Qowaidul Imla PBA UNHASY Jombang - Fani Fathanah; Muassomah (LP2M IAI NURUL HAKIM, 2022)
This paper examines the methods that will be used in delivering material so that the delivery of a material runs smoothly, thus learning Arabic will avoid the linguistic and non-linguistic problems. In order for learning to be independent of existing problems, educators / lecturers should use a learning method that can increase the learning interest of students in Arabic, especially in their writing skills (Maharah Kitabah). One method that can be used to increase interest in learning in the maharah of the qowaidul imla course is the make a match method. This paper contains several focus issues, namely how to apply the make a match method, can the make a match method increase interest in learning in writing skills (Maharah Kitabah) in the qowaidul imla course PBA Unhasy Jombang. Through descriptive qualitative research methods, and based on the focus of the problem above, in accordance with the objectives of this research, we want to see the application of suitable methods used with obstacles found in the field. So, the make a match method is one method that can be used in all subjects and can answer existing problems.